Competition Between Tumor and Mononuclear Phagocyte System Causing the Low Tumor Distribution of Nanoparticles and Strategies to Improve Tumor Accumulation - Yang, Bin; Han, Xiaopeng; Ji, Bin; Lu, Rong (Current Drug Delivery, 2016)
In the past few decades, nanoparticles have shown their advantages in anti-cancer therapy. After intravenous injection, they could preferentially arrive at tumor tissue either by extravasation from tumor vasculature or targeting vascular endothelial cells. But at the same time, their quantity in mononuclear phagocyte system (MPS) is far more than that in tumor. In this review, we discuss the advantages of MPS in spleen and liver over tumor on competing nanoparticles. The biophysical causes of spleen and liver help the MPS to capture nanoparticles, such as sufficient flux of blood stream, capillary network with fenestrations in liver and venous sinuses in spleen. Meanwhile, liver and spleen are the two major organs that contain MPS. Various properties of nanoparticles may affect their biodistribution. It is suggested that nanoparticles with proper size and shape, suitable charge, polyethyleneglycol and ligands will minimize the clearance by MPS. Several novel and promising approaches for cancer therapy are introduced in this review. This review seeks to provide guidelines for improving nanoparticles accumulation in tumor through both optimizing nanoparticles design and novel ways to design nanodelivery system for cancer therapy.
Keywords: mononuclear phagocyte system